Dinâmica de barreiras costeiras na costa semiárida brasileira: o caso do litoral de Acaraú e Itarema - Ceará - Moura, Francisco José Maciel de (2018)
Coastal barriers are sedimentary bodies that emerge near the coast and may or may not be connected to the continent, being among the most dynamic and changeable depositional features of the coastal system. They are important mainly because they offer natural shoreline protection against the direct effect of the abrasive action of waves and storms. The Brazilian Semiarid Coast, between Cabo Calcanhar (RN) and Ponta dos Mangues Secos (MA), presents well developed systems of coastal barriers, but with few studies with a specific focus on these systems. The municipalities of Acaraú and Itarema, on the West Coast of Ceará, present the most prominent system of coastal barriers of the state and one of the most expressive of all the northern Brazilian coast. Its accelerated displacement can cause, among other consequences, the greater exposure of the coastal zone to the erosive processes. In this way, the objective of this work was to understand the morphological and sedimentary dynamics of a system of coastal barriers in the Brazilian Semiarid Coast, taking as a case study the coast of the municipalities of Acaraú and Itarema, in the state of Ceará. The hypothesis raised in this work, which came to be confirmed, was that the coastal barriers of Acaraú and Itarema have presented in the last decades significant morphological and sedimentary alterations associated mainly to their migratory dynamics, implying in the general reduction of their area and in the reconfiguration morphological, which may make the said coast more exposed and, consequently, more susceptible to multiple climatic-oceanographic conditions and events. Current satellite images were used to identify the occurrence of coastal barriers along the Brazilian Semiarid Coast (approximately 1,100 km) and characterization of the main forms of use and occupation. For the analysis of the migratory process and the main morphological changes of the coastal barriers of Acaraú and Itarema on an interdecadal scale, eight coastal spit barriers were selected, analyzed over a period of 44 years (1973/1985/1993/2007/2017 ), using the satellite images of the Landsat series, chosen from the application of the methodology of standard years, which classifies the different years on a scale that varies from super wet to super dry. From this, the rate of change of the coastline was calculated by means of the method of the polygon of change (Change polygon). For the evaluation of the seasonal migratory process of a spit-barrier system and associated coastline in the coast of Itarema, four quarterly field survey campaigns (April / July / October 2016 and January 2017) were carried out in a spit- barrier island of approximately 5.7 km of lateral extension and sheltered coastline of approximately 4.3 km of lateral extension. In each campaign geodesic GPS of the type DGPS (Differential Global Positioning System) was used, assessing high precision and accuracy to the data of coastline variation. To understand the seasonal morphosedimentary behavior of a spit-barrier system and associated coastline in the coast of Itarema, 40 perpendicular topographic profiles were performed in the four field campaigns, with 10 profiles per campaign (5 in the spit-barrier island system and 5 in the sheltered coastline), through the use of DGPS, in addition to the collection and granulometric and geochemical analysis of 96 samples of uncolored surface sediments, referring to the entire monitoring period. Information about the seasonal behavior of the hydrodynamic agents and the wind turbine processes, specifically data related to the height, period and direction of waves, as well as wind direction parameters were also collected. In order to determine the sedimentation cycles in the spit-barrier system and associated coastline in the coast of Itarema from the substrate witness, 10 samples were collected, described and analyzed in different sectors, from georeferencing of the sampling points. The identification of the occurrence of coastal barriers in the Brazilian Semiarid Coast and characterization of the main forms of use and occupation allowed an unprecedented analysis of the spatial distribution and morphology patterns, with 39 spits and 9 barrier islands identified. The state of Ceará concentrates most of the spits (26, out of 39), while Rio Grande do Norte concentrates most of the barrier islands (6, out of 9). It was found that the spits of the Brazilian Semiarid Coast are more affected by anthropic pressures and present greater environmental limitations than the barrier islands, probably due to the greater difficulty of access and the most significant changes in the morphological configuration presented by the islands. The analysis of the migratory process and interdecadal morphological changes related to the coastal barriers of Acaraú and Itarema indicated the intensification of the movement dynamics and changes in the morphological pattern of these barriers in the last four decades. The performance of erosive processes has caused substantial area losses and morphological reconfiguration in practically all the coastal barriers of this region. In the last 44 years, more than 1.5 million m² were lost, representing a value superior to 36% reduction of the total initial area of the spits. The high mobility to which these spits are subjected may therefore mean not only their disappearance but also many sectors of the coastline to the backbarrier. The evaluation of the seasonal migratory process of a spit-barrier system and associated coastline in the coast of Itarema indicated the significant protective role played by the coastal barrier and that the erosive processes occurring on an interdecadal scale tend to intensify also seasonally on an annual scale , whose reflections are also experienced by the coastline, which despite being sheltered begins to present sectors with erosive tendencies. The understanding of the seasonal morphosedimentary behavior of a spit-barrier system and associated coastline in the coast of Itarema indicated that the coastal barrier presents greater morphodynamic variability, whose extremities are highly vulnerable to the migratory and erosive processes, a fact attested by the successive phases between spit and barrier island that you experience. Even the central sector of the barrier is susceptible to erosive processes due to the overwashing of the coastline during high energy events. The emergence of a sandy bar in the sheltered area near the east end indicates that the barrier island is close to being reconfigured as spit. The predominant sedimentary composition is sand and sand with sparse gravel, containing grains without a defined selection pattern due to high morphogenesis and different hydrodynamic and morphodynamic agents. The coastline presented a more stable morphodynamic behavior, with flat profiles, but less extensive because it was confined. The predominance of the thinner sediments compared to the spit-barrier system, with 88% of the samples including fine sand, very fine sand or silt, revealed the sedimentary behavior differentiated by a sheltered coastline, but in many sectors more intense erosion processes were recorded, together with the processes that occur in the coastal barrier and the probable action of more intense tidal currents. The analysis of the ten samples allowed the identification of the sedimentary facies and the interpretation of the mode of occurrence and succession of the different layers, and 8.38.5 meters of layer of sediments were recovered and analyzed.